2017
DOI: 10.1016/j.ejpb.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Poloxamer-based thermoresponsive ketorolac tromethamine in situ gel preparations: Design, characterisation, toxicity and transcorneal permeation studies

Abstract: , Poloxamer-based thermoresponsive ketorolac tromethamine in situ gel preparations: Design, characterisation, toxicity and transcorneal permeation studies, European Journal of Pharmaceutics and Biopharmaceutics (2017), doi: http://dx.doi.org/10. 1016/j.ejpb.2017.01.008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 56 publications
(64 reference statements)
6
61
0
Order By: Relevance
“…4); when poloxamer 407 concentration increases there was a significant reduction in gelation temperature (*p less than 0.05). This is consistent with many works [20][21][22][23]. Park et al found a linear relationship between P407 concentration and sol-gel transition temperature over a concentration range of 10-25%; the transition temperature is linearly reduced when P407 concentration has been increased [24].…”
Section: Fig 3: Phase Change or Solution-gel Transition At Differentsupporting
confidence: 92%
“…4); when poloxamer 407 concentration increases there was a significant reduction in gelation temperature (*p less than 0.05). This is consistent with many works [20][21][22][23]. Park et al found a linear relationship between P407 concentration and sol-gel transition temperature over a concentration range of 10-25%; the transition temperature is linearly reduced when P407 concentration has been increased [24].…”
Section: Fig 3: Phase Change or Solution-gel Transition At Differentsupporting
confidence: 92%
“…The use of poloxamer 407 results in clear, colorless, transparent gels. Transparency is a highly desirable characteristic in ophthalmic formulations because non-transparent systems may blur the vision and they are not suitable for patients [ 140 ]. Gels containing the co-polymer demonstrated muco-mimetic properties and optical clarity, promoting a significant degree of ocular permeation and an increase in the bioavailability of the drugs [ 72 ].…”
Section: Poloxamer 407-based Mucoadhesive Formulationsmentioning
confidence: 99%
“…Fathalla Z.M.A. et al [32] studied the blend of the same two poloxamers for a controlled ocular delivery of ketorolac tromethamine (KT). The most promising gel formulations, loaded with KT, were those containing the mixtures of P407:P188 23:10 w/v% and 23:15 w/v% respectively.…”
Section: Poloxamers For Oftalmic Administrationmentioning
confidence: 99%